República das crianças: novas experiências de ressocialização de crianças e adolescentes - Santos, Penelope Duarte dos (1994)
This study describer a group of educators exper ience. I t is a proposal of a pedagogical act ion toward boys and girls that live on streets. In the course of experience, althought the dificulties, the group observed a personal development - seIf steem and seIf reIiance increasing - and also a collective progress - sociaIization and habits and attitudes acquiring. This project was an innovator pedagogical experience whereas privileged alternatives soIutions to educate children and adolescent that Iive on streets.